2019
DOI: 10.4034/pboci.2019.191.29
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer and Anti-Proliferation Activity of Ethyl Asetat Extract From Ant Nest (Myrmecodia pendans) in Burkitt’s Lymphoma Cancer Cells

Abstract: Objective: To determine the activity of anti-cancer and anti-proliferation of ethyl acetate fraction of ant nest plants (Myrmecodia pendans) in Burkitt's Lymphoma cancer cells. Material and Methods: The study was conducted in a pure laboratory experimental method using Burkitt's Lymphoma cancer cell culture. Gradual research begins with the determination, extraction and fractionation of ant nest plants, to test for proliferation barriers. Data analysis using two-way ANOVA followed by Post Hoc LSD test with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Notably, these values are lower than those reported for other ant venoms with anticancer effects. For instance, the study of fire ant ( Solenopsis invicta ) venom on endothelial cells reported an IC50 of 3 μg/mL [ 30 ], while the study of Achmad et al [ 31 ], testing the inhibition of Burkitt’s Lymphoma cell proliferation using ant nest ethyl acetate extract, reported inhibition of cell growth at the lowest concentration of 15.625 µg/mL. The IC50 of Bee ( A. mellifera ) venom on MDA-MB-231 was also higher (6.25 and 3.125 μg/mL) than that observed in the current study [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these values are lower than those reported for other ant venoms with anticancer effects. For instance, the study of fire ant ( Solenopsis invicta ) venom on endothelial cells reported an IC50 of 3 μg/mL [ 30 ], while the study of Achmad et al [ 31 ], testing the inhibition of Burkitt’s Lymphoma cell proliferation using ant nest ethyl acetate extract, reported inhibition of cell growth at the lowest concentration of 15.625 µg/mL. The IC50 of Bee ( A. mellifera ) venom on MDA-MB-231 was also higher (6.25 and 3.125 μg/mL) than that observed in the current study [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many assays have been used to evaluate the toxicity activities of Myrmecodia species that associated with the potential of anticancer activity. Some crude extracts and compounds showed the inhibitory activity against various in vitro cancer cell lines (Table 2) [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58]. Besides, Suharyanto and Purwono reported that M. pendens had effective anticancer activity in vivo model series.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Burkitt's lymphoma is among most common cancers worldwide (Al-Attar et al, 1979;Achmad et al, 2019). Like all cancers, conventional treatment for lymphomas with immunotherapy and chemotherapy often lack efficacy due to the development of cancer resistance to the compounds.…”
Section: Introductionmentioning
confidence: 99%